A checklist of the benthic and epiphytic marine dinoflagellates of New Zealand, including Rangitāhua/Kermadec Islands. Issue 2 (3rd April 2019) - Rhodes, Lesley; Smith, Kirsty F.
ABSTRACT: New Zealand benthic and epiphytic dinoflagellate records increased in recent years as harmful algal bloom research increased. This was largely due to risk assessments of micro-algal biotoxins for the seafood industry and concerns regarding ciguatera fish poisoning in humans from toxic finfish. High-throughput sequencing enabled the detection of dinoflagellate species that were previously overlooked by microscopy, particularly where diatoms or sediments obscured visual identification. This checklist includes new species records for New Zealand and species usually considered planktonic, but which have benthic life stages. Thirty-one dinoflagellate genera were recorded from isolations and descriptions of living cells: Alexandrium, Amphidinium, Archaeperidinium, Azadinium, Biecheleria, Blastodinium, Bysmatrum, Coolia, Crypthecodinium, Cryptoperidiniopsis, Durinskia, Ensiculifera, Fukuyoa, Gambierdiscus, Gymnodinium, Gyrodinium, Heterocapsa, Karenia, Kryptoperidinium, Ostreopsis, Pelagodinium, Pentapharsodinium, Pfiesteria, Polarella, Prorocentrum, Protodinium, Protoperidinium, Pseudopfiesteria, Scrippsiella, Togula and Vulcanodinium . A further nine genera were detected by high-throughput sequencing: Cachonina, Dinophysis, Fragilidium, Gonyaulax, Karlodinium, Lepidodinium, Protodinium, Symbiodinium and Woloszynskia .